¿Educar al indígena? El Partido Civil y los jóvenes reformistas a inicios de la República Aristocrática - Ccahuana Córdova, Jorge Alberto (2014)
In the late nineteenth century, Peru began a process of political stabilization, which was based on an alliance between the coastal oligarchy and the Andean gamonales. The latter would retain control of indigenous masses in exchange for enjoying a position of power in Parliament and having jurisdiction, viathe provincial and local governments, over matters of education and health. However, as discussed in this article, in the early twentieth century, a faction of the Partido Civil sought to restore administrative centralization in order to make its educational project more feasible. This new proposal challenged the interests of regional elites, who saw a threat to their positions of power, as well as other factions of the Partido Civil.